Satisfaction and Difficulties of Korean Family Medicine Resident Training Faculty - Kim, Jung-Ha; Kim, Ju Young; Kwon, Kil Young; Lee, Chul-Min; Jeon, Tae-Hee; Hyun, Seung Soo (Korean journal of family medicine, 2013)
Practitioners of family medicine are essential to primary care practices in Korea. Resident training staffs in Korean family medicine departments have a crucial role in producing well-trained family physicians. This study assesses the aspects of satisfaction and difficulties of Korean family medicine resident training staffs. We surveyed the resident training staffs of various Korean family medicine departments using an online survey tool. The survey used in this study was modified from previously used questionnaires. Respondents rated items using a five-point Likert scale and a 0-10 visual analogue scale. The response rate was 43.9% (122/278). The mean satisfaction score with regard to current family medicine residency programs was 7.59 out of 10. Resident training staffs found the administrative aspects of their role to be the most difficult. There were considerable differences in the reported difficulties of resident training according to the differing characteristics of each staff member, including age, sex, type of hospital, number of staff members, role as chief, and duration of staff. Most respondents (91.9%) cited a need for faculty development programs. Korean family medicine resident training staffs need faculty development programs for the improvement of resident training. For the strengthening of core competencies among resident training staffs, faculty development programs or courses should be designed and implemented in Korea.